Is spinelessness a stable character in cactus pear cultivars? Implications for invasiveness. (January 2019) - Novoa, Ana; Flepu, Vuyolwethu; Boatwright, James S.
Abstract: Selection against invasiveness allows breeders to continue trading with plant cultivars when the wild species is otherwise invasive. However, to ensure the benefits of a species over the medium-to longer-term, it is necessary to determine whether the selected non-invasive traits are stable characters in the developed cultivars. This is especially true for Opuntia ficus-indica which provides a variety of benefits, especially in the arid and semiarid areas of the world. It does, however, also have a long history of invasion outside its native range, where it causes a wide range of negative impacts. Since the 19th century, spineless cultivars of O. ficus-indica have been developed through plant breeding. Due to their lack of spines, these cultivars can be easily grazed by herbivores and so are generally thought not to cause invasions. Spineless forms are currently widely cultivated worldwide. Nevertheless, if these cultivars were to revert to the spiny form, they could lead to future invasions. We performed germination experiments to explore the likelihood of reversion to spiny forms of nine common spineless O. ficus-indica cultivars. All seedlings grown from spineless cultivars were spiny. Overall, we suggest that further research and a risk analysis process for spineless O. ficus-indica cultivars should be developed. Highlights: The majority of spineless varieties of O. ficus-indica will revert to spininess when grown from seeds. Passing through the digestive tract of an animal is not required for the germination of O. ficus-indica seeds. Seeds from the cultivar 'Rossa' did not germinate in this experiment. Further studies need to be carried out to understand this perceived seed sterility. A risk analysis process for spineless O. ficus-indica cultivars should be developed.